Cyclic Organic Peroxides as New Fungicides against Phytopathogenic Fungi - Ivan A. Yaremenko; Peter S. Radulov; Yulia Yu. Belyakova; Dmitrii I. Fomenkov; Vera A. Vil’; Maria A. Kuznetsova; Valentina N. Demidova; Alexei P. Glinushkin; Alexander O. Terent’ev (Agrochemicals, 2023)
The search for new classes of fungicides has long been important in plant protection due to the development of fungal resistance to currently used agrochemicals. Organic peroxides have long been regarded as exotic and unstable compounds. The discovery of the antimalarial activity of the peroxide natural product Artemisinin, an achievement that was recently recognized with the Nobel Prize, has brought organic peroxides into the medicinal and agrochemistry. In this paper, fungicidal activity of synthesized organic peroxides—geminal bishydroperoxide, bridged 1,2,4,5-tetraoxanes, and tricyclic monoperoxides—were tested in vitro against an important species of phytopathogenic fungi (F. culmorum, R. solani, A. solani, P. infestans, C. coccodes). We discovered that substituted bridged 1,2,4,5-tetraoxanes exhibit fungicidal activity comparable or superior to azoxystrobin and superior to geminal bishydroperoxide and tricyclic monoperoxides. The contact mode of action was demonstrated for the bridged 1,2,4,5-tetraoxane.